Acute pancreatitis and its association with dyslipidemia - Gudas Ravinder; Ramchandraiah Chintalaboguda; Sanjeev Kumar Adepu (Asian Journal of Medical Sciences, 2022)
Background: Pancreatitis is described as any inflammation that manifests in acute or chronic forms in the pancreas. Acute pancreatitis (AP) is a quick attack that results in pancreatic inflammation and affects the peripancreatic tissue and surrounding organ.